Carbon nanotube torsional springs for regenerative braking systems. (24th September 2015) - Liu, Sanwei; Martin, Corbin; Lashmore, David; Schauer, Mark; Livermore, Carol
Abstract: The modeling and demonstration of large stroke, high energy density and high power density torsional springs based on carbon nanotube (CNT) yarns is reported, as well as their application as energy-storing actuators for regenerative braking systems. An originally untwisted CNT yarn is cyclically loaded and unloaded in torsion, with the maximum rotation angle increasing incrementally until failure. The measured average extractable energy density values are 2.9 kJ kg −1 ± 1.2 kJ kg −1 and 3.4 kJ kg −1 ± 0.4 kJ kg −1 for 1-ply CNT yarns and 2-ply CNT yarns, respectively. Additionally, a regenerative braking system is demonstrated to capture the kinetic energy of a wheel and store it as elastic energy in twisted CNT yarns. When the yarn's twist is released, the stored energy reaccelerates the wheel. The measured energy and mean power densities of the CNT yarns in the simple regenerative braking setup are on average 3.3 kJ kg −1 and 0.67 kW kg −1, respectively, with maximum measured values of up to 4.7 kJ kg −1 and 1.2 kW kg −1, respectively. A slightly lower energy density of up to 1.2 kJ kg −1 and a 0.29 kW kg −1 mean power density are measured for CNT yarns in a more complex setup that mimics a unidirectional rotating regenerative braking mechanism.